Political Economy Analysis of how Corruption affects Climate Change Adaptation and Mitigation. A Case Study of the Forest and Land Use Sectors of Ghana - Patrick Opoku; Henry Mensah; Dorcas Peggy Somuah; Dorothy Asabea Opoku; Rudith King (African Journal on Land Policy and Geospatial Sciences, 2022)
Context and background Land and forest play a critical role in climate change since a rise in deforestation and land degradation contributes to greenhouse gas emissions and global warming. If there is one thing that will sabotage efforts to address deforestation and the climate crisis, it is corruption. Yet corruption is strangely missing from the discussions and academic literature on forest and lands in many countries. In Ghana, how corruption in the land and forestry sectors affect climate change adaptation and mitigation has received very little attention. This study addresses this issue from a theoretical and empirical stand points. Goal and Objectives: The objectives of the study are (a) to assess the causes and types of corruption in the forestry and land use sector and (b) to analyze how these types of corruption affect climate change adaptation and mitigation, and (c) to assess the anti-corruption measures in place to deal with these types corruption. Methodology: The study adopted a mixed method approach involving a review of relevant literature on forest and land governance in Ghana as well as a review of literature on corruption and climate change. This was supported with expert interviews and discussions. Results The study found out that different types of corruption exist in the forestry and land use sector that affect climate change adaptation and mitigation including elite capture of benefits from climate change programs, extortion of money for land services, bribery of forestry officials, kick-back and rent-seeking. Existing anti-corruption structures in place have not been effective in dealing with these types of corruption in Ghana due to weak judicial system, politicization of corruption and crime and lack of political will to enforce laws. The study recommends depoliticization of corruption, enforcement of anti-corruption laws and empowerment of local stakeholders to play the watch-dog role.